The semantic dissolution of the structure in ME shulen on its path to epistemicity - Wawrzyniak, Agnieszka (Adam Mickiewicz University, 2006)
The present paper based on Chaucer’s “Canterbury Tales” offers a historical analysis of the semantic development of ME shulen with particular attention paid to the emergence of its future and epistemic senses. The study will juxtapose the analysis of OE sculan with ME shulen. In the drawn comparison, the paper will indicate that OE sculan was contextually contingent and constituted a structure, contrary to ME shulen which was contextually free. Moreover, the development of the ME sense of futurity when compared with the OE sense of prophecy, is to be viewed as the increase in the level of abstractness via defocusing of the divine conceptual subject. Furthermore, the present study will illustrate that the mechanism that affected the changes and led to the grammaticalisation process where neither purely metaphorical nor metonymic but metaphorical perspectivised metonymically thereby giving rise to “the emerging metaphor” (Radden 2003).